2018
DOI: 10.1155/2018/5189761
|View full text |Cite
|
Sign up to set email alerts
|

Trueness and Precision of Three-Dimensional Digitizing Intraoral Devices

Abstract: Aim To measure the trueness and precision under repeatable conditions for different intraoral scanners (IOSs) when scanning fully edentulous arch with multiple implants. Materials and Methods Three IOSs and one industrial scanner were used to scan one edentulous master cast containing five implant scan bodies and three spheres. The cast was scanned thirty times with each scanner device. All scans were analyzed in the inspect software, and three-dimensional locations of the implants and the interarch distance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 17 publications
(29 reference statements)
4
34
0
Order By: Relevance
“…The increasing inaccuracies of the teeth 24 and 26 could be explained due to the longer scanning path. Similar results were also reported by (18) and (19). These results were confirmed in the in-vivo part of the present study.…”
Section: Digital Impressionsupporting
confidence: 94%
See 1 more Smart Citation
“…The increasing inaccuracies of the teeth 24 and 26 could be explained due to the longer scanning path. Similar results were also reported by (18) and (19). These results were confirmed in the in-vivo part of the present study.…”
Section: Digital Impressionsupporting
confidence: 94%
“…For the patient 1, the highest deviation could be observed between the implant in regio 36 and the implant in regio 46, this was likewise the longest scanning distance. Patient 3 also showed the greatest inaccuracies between the longest distance (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In contrast to the in-vitro part, however, the digital impressions achieved partially results more precise.…”
Section: Digital Impressionmentioning
confidence: 94%
“…The mathematical error increased in the transition from single crown to partial prosthesis up to full-arch, both in trueness and in precision. A similar study was done by Braian et al [51], wherein they studied the trueness and precision under repeatable conditions for different IOSs when scanning fully edentulous arches with multiple implants, and they found low precision when scanning fully edentulous arches with multiple implants. This result is similar to our study: as the scanning length increased, the accuracy decreased.…”
Section: Discussionmentioning
confidence: 65%
“…e simulator contributes to the higher accuracy of IOS. Mutwalli et al [24] studied the trueness and precision of different IOS when scanning fully edentulous arch with multiple implants. ey found that there were significant differences between all IOS.…”
Section: Discussionmentioning
confidence: 99%